Towards ultralow platinum loading proton exchange membrane fuel cells. Issue 4 (25th January 2023) - Fan, Linhao; Deng, Hao; Zhang, Yingguang; Du, Qing; Leung, Dennis Y. C.; Wang, Yun; Jiao, Kui
Abstract : In-depth discussions on the motivation and latest advancements for designing ultralow platinum loading PEMFCs, along with the important technical routes and development procedures. Abstract : With the upcoming worldwide commercialization of proton exchange membrane fuel cells (PEMFCs), the challenges regarding their cost, performance and durability urgently need to be overcome. Developing ultralow platinum (Pt) loading PEMFCs is a critical technical route to improve their cost competitiveness. This perspective provides in-depth discussion and insights on the motivation for an ultralow Pt loading of less than 0.05 grams per kilowatt, along with important technical development routes. The latest advancements for designing catalyst layers are presented regarding the critical mass transfer and degradation issues under low Pt loading. Moreover, approaches for accelerating catalyst layer development, including material development, structure design, and preparation technology, are proposed to meet the ultralow Pt loading target, which are expected to be implemented in next-generation catalyst layers for PEMFCs.